Trading Activity and Rate of Convergence in Commodity Futures Markets. Issue 9 (14th December 2016) - Bosch, David; Pradkhan, Elina
Abstract : We analyze whether and how the trading activity of different trader types impacts the rate of convergence between spot and futures markets for a broad range of commodity futures markets over the 1999–2014 period. There is strong evidence that speculators (commodity index traders) increase (reduce) the rate of convergence between spot and futures markets. © 2016 Wiley Periodicals, Inc. Jrl Fut Mark 37:930–938, 2017